The ancient inhabitants of the Chonos Archipelago (∼43°-47°S): Characterization of maritime hunter-gatherers from Western Patagonia using mitochondrial DNA - Moraga, Mauricio; de la Fuente, Constanza; Galimany, Jacqueline; Orellana-Soto, Michael; Reyes, Omar (My University, 2023)
Background: Within the southern end of South America, Western Patagonia arises as an intricate region of channels, fjords, and islands. This region holds evidence of human occupation since ca. 14,500 cal years BP, with distinctive maritime adaptations developing around 7300 cal years BP. Historically, three major populations were characterized as part of these maritime traditions: Yarnana, Kawesqar, and Chono. The arrival of European population had a profound impact in these communities, affecting their lifestyles, territory and population size and health. The northernmost populations, living within the Chonos Archipelago, were the most affected and the least known communities from Western Patagonia. Objectives: This research aims to characterize the mitochondrial DNA diversity of ancient individuals from the Chonos Archipelago, evaluating their genetic affinities with other ancient and present-day populations from Patagonia. Materials and Methods: A total of 46 individuals from the region were sampled for ancient DNA analysis. Mitochondrial DNA haplogroups were characterized and compared with ancient and present-day populations from Southern South America. Results: All individuals from the Chonos Archipelago belong to C and D haplogroups, particularly to C1b, C1b13, D1, D1g, and D4h3a5. As a group, the individuals from Chonos Archipelago lay closer to ancient individuals from Kawesqar territory, immediately south of them. Using mitogenomes, we characterized two new D4h3a5 lineages almost exclusively associated with populations from Western Patagonia. Discussion: Our results contribute to the understanding of the peopling and human interactions in Western Patagonia, suggesting these unique maritime traditions developed within local populations, genetically associated with earlier terrestrial populations.
Keywords: ancient dna; archipelagic peopling; maritime adaptations; mid and late holocene; western patagonian channels